Approaches to Determining the Liver Volume and the Fact of Hepatomegalia - A. I. Gromov; E. L. Alliua; N. S. Kul'berg (Вестник рентгенологии и радиологии)
Objective: to increase the accuracy of computed tomography (CT) in the diagnosis of hepatomegaly.Material and methods. The investigation is based on the analysis of the results of 603 abdominal CT examinations, which are available in the radiology information systems of the city of Moscow. Six liver parameters (the transverse, vertical, and anteroposterior dimensions of the right and left lobes) were measured. The volume of the organ, the right and left lobes was determined when building three-dimensional images with an IntelliSpace Portal multimodality station (Philips) and a special Synapse 3D software system (Fuji).Results. It was established that there was the most pronounced relationship to the true liver volume among all sizes when using only one parameter for the anteroposterior size of the right lobe (r = 0.66), the sum of the two ones for the vertical and anteroposterior sizes of the right lobe (r = 0.83), the sum of three sizes for the vertical, anteroposterior, and transverse dimensions of the right lobe (r = 0.86). ROC analysis was used to calculate the threshold values of the sum of two and three proposed parameters (34 and 42 cm, respectively). The sensitivity of the technique in identifying hepatomegaly, which was established on the basis of the sum of the vertical and anteroposterior dimensions of the right lobe, compared with only one-parameter orientation, increased from 26% to 87%; the specificity rose from 53% to 86%; when using the sum of the vertical, anteroposterior, and transverse dimensions of the right lobe, that was as much as 89% and 84%, respectively. Approximating the cubic root of the volume with the least squares method allowed one to create new and convenient formulas for calculating the volume of the liver.Conclusion. Determination of the sum of the vertical and anteroposterior dimensions of the right lobe (threshold value, 34 cm) is an optimal approach to diagnosing hepatomegaly. If there is a need for knowledge of the volume of the liver in the absence of special programs for its segmentation, data can be obtained using the created formula that takes into account two proposed liver sizes.